Characteristics of environmental degradation in mining areas (A case study of the Southern Trans-Urals) - Aufar Gareev; Emil Gareev (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
The areas affected by mining operations are characterized by extremely complex environmental changes that affect all components of the natural complexes. In several cases, radical negative changes (transformations) take place, which cause the formation of the habitat, characterized by changes in characteristics of all components of the natural environment, including geological structure, soil cover, surface and groundwater and atmospheric air, respectively, flora and fauna. This generally leads to a sharp deterioration of ecological conditions, including living conditions of living organisms and human habitation, causing stressful situations, inconveniences, as well as characteristic diseases due to the influence of factors of excessive pollution of components of the natural environment. As one of the objects of the study, the impact zone of mining enterprises within the town of Sibai and its surroundings in the Republic of Bashkortostan was chosen. It is typical for the assessment of occurring changes and other industrial centers and districts located within the vast strip of the Southern Urals. It has been revealed that the greatest damage is inflicted on ecosystems of small rivers, which is caused by both direct and indirect entry of pollutants into them as a result of dissolution, leaching and entry from rock dumps, emissions into the atmosphere, and settling on the surface of soil and snow cover; direct discharge of wastewater into them, etc. It is shown that with the lingering impact of the regional response to global climate change, environmental problems are exacerbated. This calls for urgent measures to restore favorable environmental conditions and address a wide range of economic and social problems.